A composite solid electrolyte with an asymmetric ceramic framework for dendrite-free all-solid-state Li metal batteries. Issue 15 (1st April 2021) - Lin, Yanke; Liu, Ke; Xiong, Cheng; Wu, Maochun; Zhao, Tianshou
Abstract : A novel CSE with an asymmetric dual-layer ceramic framework was developed to simultaneously improve the ionic conductivity of solid electrolytes and ameliorate the Li dendrite formation in ASSLMBs. Abstract : Composite solid electrolytes (CSEs) that inherit desirable features from both ceramic and polymer electrolytes are promising to realize all-solid-state Li metal batteries with enhanced energy density and safety. However, conventional CSEs formed by mechanically mixing ceramics and polymers not only suffer from low ionic conductivity but also trigger a non-uniform ion distribution at the interface, resulting in a large internal resistance and severe dendrite growth. To address these two issues simultaneously, here, we develop a novel CSE with an asymmetric dual-layer Li1.3 Al0.3 Ti1.7 (PO4 )3 ceramic framework (dual-layer CSE). The vertically-aligned porous layer of the framework provides expressways for Li + ion conduction, endowing the CSE with a high ionic conductivity of 0.101 mS cm −1 at 25 °C, while the thin dense layer is designed to homogenize the ion distribution at the interface facing the Li anode, allowing uniform Li electrodeposition. As a result, a dendrite-free Li metal anode with stable stripping/plating for over 500 h at 0.4 mA cm −2 is obtained, and the assembled all-solid-state Li/dual-layer CSE/LFP battery achieves a high capacity of 143.5 mA h g −1 at 1C without obvious decay even after 500 cycles. This work offers not only an innovative design but also fundamental insights into novel CSEs with high conductivity and dendrite suppression capability, which paves the way for the development of dendrite-free, long lifespan all-solid-state Li metal batteries.